113 Improving Intravenous Fluid Therapy to Reduce the Incidence of Acute Kidney Injury in Elderly Hip Fracture Patients. (16th March 2021) - McCann, C; Hall, A; Leow, J Min; Harris, A; Hafiz, N; Myers, K; Amin, A; MacLullich, A
Abstract: Background: Acute kidney injury (AKI) in hip fracture patients is associated with morbidity, mortality, and increased length of stay. To avoid this our unit policy recommends maintenance crystalloid IV fluids of >62.5 mL/Hr for hip fracture patients. However, audits have shown that many patients still receive inadequate IV fluids. Methods: Three prospective audits, each including 100 consecutive acute hip fracture patients aged >55, were completed with interventional measures employed between each cycle. Data collection points included details of IV fluid administration and pre/post-operative presence of AKI. Interventions between cycles included a revised checklist for admissions with a structured ward round tool for post-take ward round and various educational measures for Emergency Department, nursing and admitting team staff with dissemination of infographic posters, respectively. Results: Cycle 1: 64/100 (64%) patients received adequate fluids. No significant difference in developing AKI post operatively was seen in patients given adequate fluids (2/64, 3.1%) compared to inadequate fluids (4/36, 11.1%; p = 0.107). More patients with pre-operative AKI demonstrated resolution of AKI with appropriate fluid prescription (5/6, 83.3%, vs 0/4, 0%, p < 0.05) Cycle 2: Fewer patients were prescribed adequate fluids (54/100, 54%). There was no significant difference in terms of developing AKI post operatively between patients with adequate fluids (4/54, 7.4%) or inadequate fluids (2/46, 4.3%; p = 0.52). Resolution of pre-operative AKI was similar in patients with adequate or inadequate fluid administration (4/6, 67% vs 2/2, 100%). Cycle 3: More patients received adequate fluids (79/100, 79%, p < 0.05). Patients prescribed adequate fluids were less likely to develop post-operative AKI than those receiving inadequate fluids (2/79, 2.5% vs 3/21, 14.3%; p < 0.05). Discussion: This audit demonstrates the importance of administering appropriate IV fluid in hip fracture patients to avoid AKI. Improving coordination with Emergency Department and ward nursing/medical ward staff was a critical step in improving our unit's adherence to policy.